Clonal evolution in chronic lymphocytic leukemia: Analysis of correlations with IGHV mutational status, NOTCH1 mutations and clinical significance. Issue 10 (26th July 2013) - López, Cristina; Delgado, Julio; Costa, Dolors; Villamor, Neus; Navarro, Alba; Cazorla, Maite; Gómez, Cándida; Arias, Amparo; Muñoz, Concha; Cabezas, Sandra; Baumann, Tycho; Rozman, María; et al.
<x xml:space="preserve">Abstract</x> Chronic lymphocytic leukemia (CLL) is a lymphoproliferative disorder characterized with highly variable clinical course. The most common chromosomal abnormalities in CLL, using conventional and molecular cytogenetics, are trisomy 12, del(13)(q14), del(11)(q22–23), del(17)(p13), and del(6)(q21). Whereas the prognostic marker such as IGHV mutational status remains stable during course of the diseases, chromosomal aberrations may be acquired over time. The aim of this study was to determine the incidence, and biological significance of clonal evolution (CE) using conventional and molecular cytogenetics and its relationship with prognostic markers such as CD38, ZAP70, and the mutational status of IGHV and NOTCH1. One hundred and forty‐three untreated CLL patients were included in the study. The median time interval between analyses was 32 months (range 6–156 months). Forty‐seven patients (33%) had CE as evidenced by detection of new cytogenetic abnormalities during follow‐up. CE was not correlated with high expression of ZAP70, unmutated IGHV genes or NOTCH1 mutations. Multivariate analysis revealed that CE and IGHV mutation status had a significant impact on TFS. The combination of conventional and molecular cytogenetics increased the detection of CE, this phenomenon probably being a reflection of genomic instability and conferring a more aggressive clinical course. © 2013 Wiley Periodicals, Inc.